Mesenchymal Stromal Cells Facilitate Neutrophil-Trained Immunity by Reprogramming Hematopoietic Stem Cells - Julie Ng; Anna E. Marneth; Alec Griffith; Daniel Younger; Sailaja Ghanta; Alan Jiao; Gareth Willis; Junwen Han; Jewel Imani; Bailin Niu; Joshua W. Keegan; Brandon Hancock; et al. (Karger Publishers, 2023)
Novel therapeutics are urgently needed to prevent opportunistic infections in immunocompromised individuals undergoing cancer treatments or other immune-suppressive therapies. Trained immunity is a promising strategy to reduce this burden of disease. We previously demonstrated that mesenchymal stromal cells (MSCs) preconditioned with a class A CpG oligodeoxynucleotide (CpG-ODN), a Toll-like receptor 9 (TLR9) agonist, can augment emergency granulopoiesis in a murine model of neutropenic sepsis. Here, we used a chimeric mouse model to demonstrate that MSCs secrete paracrine factors that act on lineage-negative c-kit+ hematopoietic stem cells (HSCs), leaving them "poised" to enhance emergency granulopoiesis months after transplantation. Chimeric mice developed from HSCs exposed to conditioned media from MSCs and CpG-ODN-preconditioned MSCs showed significantly higher bacterial clearance and increased neutrophil granulopoiesis following lung infection than control mice. By Cleavage Under Targets and Release Using Nuclease (CUT&RUN) chromatin sequencing, we identified that MSC-conditioned media leaves H3K4me3 histone marks in HSCs at genes involved in myelopoiesis and in signaling persistence by the mTOR pathway. Both soluble factors and extracellular vesicles from MSCs mediated these effects on HSCs and proteomic analysis by mass spectrometry revealed soluble calreticulin as a potential mediator. In summary, this study demonstrates that trained immunity can be mediated by paracrine factors from MSCs to induce neutrophil-trained immunity by reprogramming HSCs for long-lasting functional changes in neutrophil-mediated antimicrobial immunity.